The biomechanical design of a gymnastics training aid for a handstand on the rings - Yeadon, M. R.; Rosamond, E. L.; Hiley, M. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
The handstand on rings is a requirement in competition routines in Men`s Artistic Gymnastics, and hence is a key skill in the development of an elite artistic gymnast. This study was carried out to establish the coaching requirements of a training aid for a handstand on the rings, to investigate the biomechanics of the handstand, to design and construct a training aid, and to assess its performance. The key requirements of a training aid for a handstand on rings were compiled from a survey of 11 national coaches. A biomechanical analysis of a handstand on rings was carried out in order to investigate the control mechanism and to inform the training aid design. The aid was designed to permit the same control mechanism to be used and was manufactured in accordance with British Standards. In order to assess the performance of the aid displacement, joint angle, and muscle activation data were used to compare handstands on the rings, floor, prototype training aid, and two other existing training aids. The results showed that a handstand on the prototype was more similar to rings than a handstand on the existing training aids. The prototype also simplified the learning of the skill.